Design, Synthesis and In Vitro Investigation of Novel Basic Celastrol Carboxamides as Bio-Inspired Leishmanicidal Agents Endowed with Inhibitory Activity against Leishmania Hsp90 - Ivan Bassanini (Biomolecules, 2021)
The natural triterpene celastrol (CE) is here used as lead compound for the design and synthesis of a panel of eleven CE carboxamides that were tested in vitro for their growth inhibitory activity against Leishmania infantum and L.tropica parasites. Among them, in vitro screening identified four basic CE carboxamides endowed with nanomolar leishmanicidal activity, against both the promastigotes and the intramacrophage Leishmania amastigotes forms. These compounds also showed low toxicity toward two human (HMEC-1 and THP-1) and one murine (BMDM) cell lines. Interestingly, the most selective CE analogue (compound 3) was also endowed with the ability to inhibit the ATPase activity of the Leishmania protein chaperone Hsp90 as demonstrated by the in vitro assay conducted on a purified, full-length recombinant protein. Preliminary investigations by comparing it with the naturally occurring Hsp90 active site inhibitor Geldanamycin (GA) in two different in vitro experiments were performed. These promising results set the basis for a future biochemical investigation of the mode of interaction of celastrol and CE-inspired compounds with Leishmania Hsp90.